Migrating Texts: The Case of Ingmar Bergman's Thirst. (3rd July 2018) - Lundén, Rolf
Abstract: The article follows the journey of one text, Thirst (1948), a modernist short story cycle by Birgit Tengroth, into Ingmar Bergman's 1949 film of the same title, and further into the novelization of the film's shooting script (1949–50). It studies the texts as independent items directed to three separate audiences. This kind of close analysis has not, so far, been devoted to the process of textual travel, of which a Bergman film was part. The investigation goes from a text of five loosely linked stories, characterized by interiority, competing points of view, expressions of female desire, to two film scripts, produced in collaboration between Bergman and Herbert Grevenius, trying to harmonize the episodic cycle through the narrative strategies of selection, integration, and addition, to, finally, the anonymous novelization leading to even further cohesion and exteriority. The process of migration is characterized by a gradual movement away from a modernist, disunified structure towards a realist form of expression. It is also noticeable that the eroticism and focus on lesbianism in the adapted text are possible to repeat and make even more explicit in the novelization of the film script, while the film does not allow for such openness. The article also emphasizes the reception of these texts by both contemporaneous and later critics.